Magnetic conjugacy of Pc1 waves and isolated proton precipitation at subauroral latitudes: importance of ionosphere as intensity modulation region - Ozaki, Mitsunori; Shiokawa, Kazuo; Horne, Richard B.; Engebretson, Mark J.; Lessard, Marc; Ogawa, Yasunobu; Hosokawa, Keisuke; Nosé, Masahito; Ebihara, Yusuke; Kadokura, Akira; Yagitani, Satoshi; Miyoshi, Yoshizumi; et al. (My University, 2021)
Pc1 geomagnetic pulsations, equivalent to electromagnetic ion cyclotron waves in the magnetosphere, display a specific amplitude modulation, though the region of the modulation remains an open issue. To classify whether the amplitude modulation has a magnetospheric or ionospheric origin, an isolated proton aurora (IPA), which is a proxy of Pc1 wave-particle interactions, is compared with the associated Pc1 waves for a geomagnetic conjugate pair, Halley Research Base in Antarctica and Nain in Canada. The temporal variation of an IPA shows a higher correlation coefficient (0.88) with Pc1 waves in the same hemisphere than that in the opposite hemisphere. This conjugate observation reveals that the classic cyclotron resonance is insufficient to determine the amplitude modulation. We suggest that direct wave radiation from the ionospheric current by IPA should also contribute to the amplitude modulation.
Keywords: Magnetic conjugacy; Pc1 waves; Proton precipitation; Subauroral latitudes